Airborne - Bean, Nigel; BBC Learning (Australia: BBC Learning, 2005)
This series visits the crucial moments in life's journey to dominate the earth.'Airborne' illustrated the four evolutions of flight
Photography, Simon wagen ; executive producer, Michael Gunton ; series producer, Miles Barton
Keywords: Flight; Animal locomotion; Birds; Birds -- Evolution; Insects; Insects -- Anatomy